Color discrimination in fixed saturation level of patients with acute traumatic injury - Nicolau da Costa, Leonardo R.; Sousa, Joyce B.; Brito, Felipe André C.; Igarashi, Yuzo; Gomes, Janildes Maria Silva; Lobão, Carlos Augusto; Costa, Marcelo Fernandes; Miquilini, Leticia; Souza, Givago Silva (Frontiers in Neurology, 2024)
Introduction Traumatic brain injury (TBI) is an important public health concern and that may lead to severe neural sequels, such as color vision deficits. Methods We evaluated the color vision of 10 TBI patients with normal cognitive function using a color discrimination test in a fixed saturation level. We also analyzed computerized tomography scans to identify the local of the brain damages. Results Four TBI patients that had lesions in brain areas of the ventral visual streams, five TBI patients had lesions inferred in brain areas of the dorsal visual stream, and one TBI patient had lesion in the occipital area. All the patients had cognitive and color vision screened and they had characterized the chromatic discrimination at high and low saturation. All participants had no significant cognitive impairment in the moment of the color vision test. Additionally, they had perfect performance for discrimination of chromatic stimulus at high saturation and similar to controls (n = 37 age-matched participants). Three of four TBI patients with lesions in the ventral brain and one patient with lesion in the occipital area had impairment of the chromatic discrimination at low saturation. All TBI patients with lesions in the dorsal brain had performance similar or slightly worse than the controls. Conclusion Chromatic discrimination at low saturation was associated to visual damage in the ventral region of the brain and is a potential tool for functional evaluation of brain damage in TBI patients.